2010
DOI: 10.2174/092986710791299957
|View full text |Cite
|
Sign up to set email alerts
|

Current Advances in Anti-Influenza Therapy

Abstract: Every year, influenza epidemics cause numerous deaths and millions of hospitalizations, but the most frightening effects are seen when new strains of the virus emerge from different species (e.g. the swine-origin influenza A/H1N1 virus), causing world-wide outbreaks of infection. Several antiviral compounds have been developed against influenza virus to interfere with specific events in the replication cycle. Among them, the inhibitors of viral uncoating (amantadine), nucleoside inhibitors (ribavirin), viral t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 139 publications
0
46
0
Order By: Relevance
“…Peramivir was briefly licensed for emergency use during the swine-origin H1N1 epidemic in an injectable formulation for patients on ventilators and is currently completing clinical trials, and several other backbones are being tested as well as further derivatives of zanamivir. Several recent reviews describe these new developments 3,5,6,6669 .…”
Section: Na Inhibitors and Resistance Mutationsmentioning
confidence: 99%
“…Peramivir was briefly licensed for emergency use during the swine-origin H1N1 epidemic in an injectable formulation for patients on ventilators and is currently completing clinical trials, and several other backbones are being tested as well as further derivatives of zanamivir. Several recent reviews describe these new developments 3,5,6,6669 .…”
Section: Na Inhibitors and Resistance Mutationsmentioning
confidence: 99%
“…At the moment, there are several proposed anti-influenza therapies based on varying strategies (Palese and GarciaSastre 2002;Saladino et al, 2010). Based on our results, we propose that designing influenza vaccines and antiviral strategies that target the twin Asn-residue could have the potential to be another anti-influenza strategy.…”
Section: Ha2 Twin Asn-residuementioning
confidence: 62%
“…Although, directly targeting viruses has been successful in controlling viral diseases, it suffers from some serious weaknesses, including failure to eliminate chronic viral myocarditis, narrow spectrum of action, and the inherent capacity to force outgrowth of drug resistance mutations (Tan et al, 2007). Thus, the discovery of novel antiviral targets, host cell-based antiviral agents is a more promising approach and deserves more attention (Saladino et al, 2010). At the cellular level, studies have shown that host cell phospho-proteins essential for viral replication, are potentially targetable [ (Marchant 2009) reviewed in ].…”
Section: Proposing Novel Therapeutic Targets For Viral Myocarditis Thmentioning
confidence: 99%